Update on benign paroxysmal positional vertigo - Kim, Hyo-Jung (J Neurol, 2020)
Benign paroxysmal positional vertigo (BPPV) is the most common cause of vertigo worldwide. This review considers recent advances in the diagnosis and management of BPPV including the use of web-based technology and artificial intelligence as well as the evidence supporting the use of vitamin D supplements for patients with BPPV and subnormal serum vitamin D.